An Interpretation Model for the Production Profile on the Same Angle of a Horizontal Well Trajectory - Song, Wenguang; Jia, Na; Jiang, Qiongqin (Frontiers in Energy Research, 2020)
An accurate interpretation of the fluid production profile is the essential scientific step required for the dynamic monitoring and management of a reservoir. Currently, an accurate interpretation of conventional logging is generally available for vertical wells. However, high-accuracy interpretation is still a blank for horizontal wells, especially for those wells with low production. Therefore, it is of great importance to develop a new model that can efficiently improve the interpretation accuracy of horizontal wells' production profiles. Practically, it was observed from experiments that, for multiphase flow in a horizontal well, the flow pattern changes significantly with the varied inclination angle along the well trajectory. This is because the flow pattern is critically related to the flow rate and the measured phase flow data (i.e., the production data of oil, gas, and water), which varies with the inclination angle along the horizontal well trajectory. Based on the above observations, a new methodology is proposed to interpret horizontal wells' production profiles with the same inclination angle. A comparison of the measured data and numerically calculated results indicates that the newly established method can significantly improve the interpretation accuracy of horizontal wells' production fluid profile. The interpretation method is, therefore, enriched by production logging for different types of wells. By comparing the experimentally measured data and the calculated results, the newly established method is indicated to be capable of significantly improving the interpretation accuracy of horizontal wells' fluid production profile. The interpretation method is further extended to production logging for different well types. By applying this new methodology, the main water-producing layer can be precisely identified to prevent and control the water burst from horizontal wells as well as the formation of water plugging. Consequently, oil and gas recovery can be effectively enhanced.